Microsatellite Primers in the Lichen Symbiotic Alga Trebouxia decolorans (Trebouxiophyceae) - Francesco Dal Grande; Andreas Beck; Garima Singh; Imke Schmitt (Applications in Plant Sciences, 2013)
Premise of the study: Polymorphic microsatellite markers were developed for the symbiotic green alga Trebouxia decolorans to study fine-scale population structure and clonal diversity.